L’animale tecnico. Compimento della metafisica nel pensiero di Heidegger - Spina, Salvatore (Mechane, 2022)
The aim of this paper is to analyze the ontological relationship between technology and metaphysics in Heidegger’s works through the question of the animality. On the one hand, the Heideggerian deconstruction of the history of philosophy give us the possibility to understand the nihilistic character of the Western; on the other hand, it shows the first signs [Winke] of a new beginning.